VALIDATION OF SIMPLE ISOCRATIC HPLC ASSAY FOR THE DETERMINATION OF CHLORTETRACYCLINE CONCENTRATION IN PLASMA OF CHICKEN - M. Nivetha; S. Ramesh; L. Kalaiselvi; R. Gokul; T. Ramasamy (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Chlortetracycline (CTC) is a broad-spectrum antibiotic belonging to the tetracycline group of drugs. It is commonly used in the poultry industry for the treatment of bacterial infections and is also used as a growth promoter. This study was aimed at validating the sensitive HPLC method for the assay of CTC in chicken plasma. The method consisted of isocratic elution with separation using a C]8 column. The mobile phase used in the study was aqueous oxalic acid (0.03M), acetonitrile and methanol in the ratio of 60:30:10. The HPLC conditions included a flow rate of Iml/min with UVdetection at 375nm. CTC in chicken plasma was extracted with Mcllvaine buffer followed by dilution with water in the ratio of 1:1 andfiltered using 0.22p filters. The peak of chlortetracycline was noticed at 5-6 minis. The method was linear from 0.05mg/ml to 10mg/ml. The recovery percentage from plasma was recorded as 110%. Thus, from this study it is inferred that this method is optimal for the assay of CTC in plasma for pharmacokinetic studies.